2015
DOI: 10.1007/s13197-015-1991-0
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the antioxidant activity and components in crude oat oil and soybean oil

Abstract: Developing new antioxidants and using natural examples is of current interest. This study evaluated the antioxidant activities and the ability to inhibit soybean oil oxidation of oat oil obtained with different solvents. Oat oil extract obtained by ethanol extraction gave the highest antioxidant activity with a DPPH radical (1,1-diphenyl-2-picrylhydrazyl) scavenging activity of 88.2 % and a reducing power (A 700) of 0.83. Oat oil extracted by ethanol contained the highest polyphenol and α-tocopherol content. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Consistent with our results, Chen et al. (2016) demonstrated that the antioxidant activity of oil was increased with increasing the solvent polarity. In other words, the extracted oil would contain higher antioxidant compounds.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with our results, Chen et al. (2016) demonstrated that the antioxidant activity of oil was increased with increasing the solvent polarity. In other words, the extracted oil would contain higher antioxidant compounds.…”
Section: Resultssupporting
confidence: 93%
“…Currently, oat is gaining in popularity due to its potential as a functional food crop and contents of health benefit promoting compounds as antioxidants, lipids and high levels of globular proteins. Oat is also well known as an excellent source of β-glucan (1-3; 1-4 mixed link β-d-glucan), a dietary fiber with documented and approved health claims regarding blood glucose stabilizing and cholesterol lowering properties (Butt et al 2008;Rasane et al 2015;Chen et al 2016). These different compounds are accumulating in the oat grain in which the endosperm tissue makes out the major and the embryo tissue only a minor part.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant potential was used for the determination of anion scavenging activity of finely ground flaxseed flour oils using DPPH (1,1-diphenyl-2-picrylhydrazyl) as reported by (Chen, H. et al,(2016))with slight modification. The absorbance was measured at 520 nm.…”
Section: In-vitro Antioxidant Activitymentioning
confidence: 99%